Management of the Indonesian Cricket Association (PCI) in East Nusa Tenggara Province - Petrus Agustinus Franco Kapitan; Soegiyanto KS; Heny Setyawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to analyze the administration of the Indonesian Cricket Association (PCI) in East Nusa Tenggara. This research method uses a qualitative analysis approach and the design of the research approach used in this study is a qualitative descriptive analysis approach. Data collection techniques for this study using observation, observation, interview, and documentation methods. Subjects in this study were managers, coaches and athletes from the Indonesian Cricket Federation in East Nusa Tenggara. The data analysis technique in this study was the use of source triangulation, and the study aimed to analyze planning, organization, implementation, and monitoring systems. The survey found that the Indonesian Cricket Federation in East Nusa Tenggara province has done a very good job of organizing. During the planning phase, we found that we needed a planning program. During the organizing stage, it was very good that all the managers of the organization fulfilled their respective duties, but it was not optimal. It was good. At the monitoring stage, the Indonesian Cricket Federation is doing very well in East Nusa Tenggara. It conducts evaluations after each activity is completed, and conducts evaluations annually.